ASEAN education cooperation: An assessment of the education divide and measuring the potential impact of its elimination - Sanchita Basu Das; Badri Narayanan (Asian Development Bank Institute (ADBI), 2022)
Quality education is a key determinant for ASEAN's aspiration to be a single market and production base and to attract foreign investment. However, the region is characterized by an education divide in terms of quality and output, and this is likely to increase in the post-COVID-19 period. A simulation, modeling a productivity increase in the education sector through an increase in the HDI-Education Index for lagging ASEAN countries to the level of Singapore (benchmark country), shows that GDP, exports, and consumption are poised to go up much more for the countries that lag farther behind Singapore in their education quality. This provides an incentive to ASEAN countries to pay more attention to education cooperation, particularly in terms of setting regional targets for improved education quality and output at national level while linking education more intrinsically to ASEAN economic cooperation.
Keywords: I21; R11; 330; ASEAN; education; economic development